The teaching methodology of Arabic speaking skills: learners’ perspectives - Che Haron, Sueraya (Canadian Center of Science and Education, 2013)
Teaching methodology plays an important role in transmitting knowledge and skills to learners. The effectiveness of both knowledge and skills depends greatly on the methodology used. This paper describes a study to investigate the learners’ perspectives on the teaching methodology used by the teachers at the Centre for Foundation Studies, International Islamic University Malaysia, to teach Arabic speaking skills. The data were collected using a focus group interview with 6 Arabic language learners at the centre. The findings show that the learners were dissatisfied with the teaching methodology as it emphasizes memorization. Instead they prefer a communicative approach where they can apply orally what they have learned, be corrected and improve.